Antifungal activities of seeds oils Acacia arabica and raddiana from the Hoggar region (southern Algeria) - Tissouras, Fatiha; Larid, Mohamed; Lotmani, Brahim (Advances in Environmental Biology, 2014)
This work aims to study the antifungal activity of crude oils seeds of Acacia arabica and Acacia raddiana arid region Hoggar (southern Algeria). At various concentrations, these oils were tested in vitro on lots ATCC Candida albicans and Aspergillus niger by two different techniques the broth dilution and diffusion in solid medium (method well). A multifactorial statistical analysis of data was made of variance (P≤0.05). Biological tests also show a strong antifungal activity beside Aspergillus niger and Candida albicans strains. The minimum inhibitory concentrations were recorded in the range 0.079 ≤ MIC ≤ 0.158 mg/ml respectively for the two oils of the species raddiana and arabica. This bioactivity is probably due to antioxidant tocopherols and the other bioactive substances to be identified and characterized by methods of mass spectrometry and NMR. However, an effect of stimulating the development of strain A. niger was found in the presence of greater than 0.158 mg/ml concentrations for oils. The stimulating effect of oils can be used in various food and pharmaceutical fields
Keywords: Acacia arabica; Acacia raddiana; antifungal activity; Aspergillus niger; Candida albicans; CMI